Intervencion del terapista respiratorio en paciente femenino de 5 años con bronquitis. - Pacheco Vera, Olga Betsaida (2023)
Bronchitis is a pathology of the respiratory tract, characterized by being an inflammatory disease at the same time, it is noted for occurring more frequently in pediatric patients, this being one of the reasons for hospitalization in health centers. The present study was based on therapeutic intervention by the respiratory therapy professional; addressed to a 5-year-old female patient who arrived at the emergency area manifesting a clinical picture of productive cough from 5 days ago, respiratory distress and fever. The objective of this study was to establish the intervention of the respiratory therapist in the 5-year-old female patient who was diagnosed with the respiratory pathology of bronchitis after carrying out several studies. Finally, the treatment, monitoring and follow-up that was carried out in this clinical study, favored the fulfillment of the programmed objectives and at the same time a favorable response was obtained in the patient's clinic, taking nebulization as the best option for treatment, complemented with respirato